KONSEP KETUHANAN DALAM KAJIAN FILSAFAT - Ning Ratna Sinta Dewi (Prodi Studi Agama-Agama, 2021)
Metaphysical theology is the study of God. God as the object of metaphysical study has a specificity compared to the other two objects of metaphysics. If the outward manifestation of the universe and the soul can be perceived by the senses, then the same is not true for the reality of divinity. God is something that cannot be grasped by the senses. Metaphysics that studies about God is called the philosophy of divinity (naturalist theology). If the philosophy of divinity makes God the final point or conclusion of the entire study, then revelation theology views God as the starting point for its discussion. The philosophy of divinity deals with proving the truth of the existence of God based on human reasoning. Divinity philosophy (naturalist theology) does not question the existence of God, the discipline only wants to underline that if there is no uncaused first cause, the relative-contingent position of objects cannot be understood by reason. From the above, there are several kinds of philosophical evidence that try to open the way to God; namely the proof of ontology, cosmology, teleology, morals, and this is at the same time an advantage of the philosophical approach compared to the approach of religion and other sciences. Science is limited to making descriptions based on empirical experience while religion departs from belief in one doctrine.